Sosialisasi Panduan Penulisan Artikel Ilmiah Menggunakan Metode Penelitian Kuantitatif - Baharuddin, Siti Ruqaiyah; Junaeda, St.; Sakmawati, Sakmawati; Siddiq, Nurul Jamiah Siddiq; Ali, A. Muh. (Jurusan Matematika FMIPA UNM, 2025)
This study aims to enhance students' understanding of writing scientific articles based on quantitative research methods. The socialization was conducted online via Zoom Meeting, supported by Google Classroom for further discussions. The event involved 80 participants from diverse academic backgrounds. The materials covered fundamental concepts of quantitative research, sampling techniques, data collection and analysis using statistical tools such as SPSS, and ethical considerations in scientific writing. Evaluation was carried out through an online survey to assess participants' comprehension of the presented material. The results indicate that this socialization provided broader insights into scientific article writing, particularly in adhering to academic standards and publication ethics. With continued mentoring, students are expected to apply quantitative methods in their research and produce high-quality publications that meet the standards of scientific journals. Keywords: quantitative research, scientific writing, data analysis, academic publication, online socialization.